2020
DOI: 10.9734/ejnfs/2020/v12i530232
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum Grains: Nutritional Composition, Functional Properties and Its Food Applications

Abstract: This review work is on the composition, functional properties and food applications of sorghum grains. The review shows that this cereal grains is a rich source of carbohydrate and starch, with little of proteins, fat, vitamins and other nutrients. The functional properties of sorghum were also explored and the findings gotten from various authors shows that sorghum has good functional properties in terms of its bulk density, oil absorption capacity, water absorption capacity, least gelatinization temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 19 publications
3
14
1
1
Order By: Relevance
“…However, the genetic variability of sorghum accessions is a factor that influences the chemical composition of the grain (Espitia-Hernández et al, 2020). Fat results were similar to those reported by Rhodes et al (2017) and Abah et al (2020), who, evaluated the chemical composition of different sorghum genotypes with different origin and found fat values in a range from 1.05% to 4.40%. Humidity results agree with those obtained by Wang et al (2019), who when analyzing sorghum flours, found an average of 10% humidity.…”
Section: Chemical Compositionsupporting
confidence: 86%
“…However, the genetic variability of sorghum accessions is a factor that influences the chemical composition of the grain (Espitia-Hernández et al, 2020). Fat results were similar to those reported by Rhodes et al (2017) and Abah et al (2020), who, evaluated the chemical composition of different sorghum genotypes with different origin and found fat values in a range from 1.05% to 4.40%. Humidity results agree with those obtained by Wang et al (2019), who when analyzing sorghum flours, found an average of 10% humidity.…”
Section: Chemical Compositionsupporting
confidence: 86%
“…More sorghum is used for biofuel and animal feed than for human consumption in the developed countries like United States, Mexico and Australia (Mundia et al 2019;Mathur et al 2017). Sorghum is rich in minerals and vitamins like B complex vitamins, magnesium (Mg), calcium (Ca), potassium (K), phosphorus (P), iron (Fe), zinc (Zn) and sodium (Na) (Abah et al 2020;Xiong et al 2019). It is also an excellent source of fiber, antioxidants and protein (Kulamarva et al 2009;Xiong et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Like a C 4 plant, sorghum has higher rate of photosynthesis and agricultural production potential than other crops. Also, it is more resistant to inhibition by oxygen and has lower photorespiration ( Serna-Saldivar, 2010 ; Abah et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%